Internet Child Sex Offenders' Concerns about Online Security and their Use of Identity Protection Technologies: A Review. (18th February 2014) - Balfe, Myles; Gallagher, Bernard; Masson, Helen; Balfe, Shane; Brugha, Ruairi; Hackett, Simon
Abstract : The purpose of this article is to review what is known about the technologies that internet child sex offenders use to abuse or exploit children, offenders' attitudes towards online security and surveillance risk, and their use of identity protection tactics and technologies. The peer‐reviewed literature on internet sex offenders published between 2000 and 2011 was surveyed. Internet child sex offenders use a mixture of new and old technologies to abuse children. Offenders' awareness of internet‐related risk appears to exist along a continuum. A number of psychological and demographic factors may influence offenders' perceptions of online security risk and their willingness to take security precautions. A surprisingly large number of apprehended offenders in the time period examined by this review did not seem to use any technologies to disguise their identities. A major research programme into internet offenders' use of identity protection technologies, and their use of technologies in general, is needed. Copyright © 2014 John Wiley & Sons, Ltd. 'Internet child sex offenders use a mixture of new and old technologies to abuse children.' Key Practitioner Messages: Internet child sex offenders use a variety of commonly available technologies, such as social networking sites and peer‐to‐peer platforms, to abuse children. Offenders are a diverse group when it comes to how they perceive risk and act on those perceptions. The risk perceptions and risk management behaviours of individual offenders can be dynamic. In the period surveyed by this review (2000–11), some studies found that surprisingly few offenders used technological measures to protect their identities. 'Surprisingly few offenders used technological measures to protect their identities.'